Neuronal Release of Cytokine IL-3 Triggered by Mechanosensitive Autostimulation of the P2X7 Receptor Is Neuroprotective - Lim, Jason C.; Lu, Wennan; Beckel, Jonathan M.; Mitchell, Claire H. (Frontiers in Cellular Neuroscience, 2016)
Mechanical strain due to increased pressure or swelling activates inflammatory responses in many neural systems. As cytokines and chemokine messengers lead to both pro-inflammatory and neuroprotective actions, understanding the signaling patterns triggered by mechanical stress may help improve overall outcomes. While cytokine signaling in neural systems is often associated with glial cells like astrocytes and microglia, the contribution of neurons themselves to the cytokine response is underappreciated and has bearing on any balanced response. Mechanical stretch of isolated neurons was previously shown to trigger ATP release through pannexin hemichannels and autostimulation of P2X7 receptors (P2X7Rs) on the neural membrane. Given that P2X7Rs are linked to cytokine activation in other cells, this study investigates the link between neuronal stretch and cytokine release through a P2X7-dependent pathway. Cytokine assays showed application of a 4% strain to isolated rat retinal ganglion cells (RGCs) released multiple cytokines. The P2X7R agonist BzATP also released multiple cytokines; IL-3, TNF-α, CXCL9, VEGF, L-selectin, IL-4, GM-CSF, IL-10, IL-1Rα, MIP and CCL20 were released by both stimuli, with the release of IL-3 greatest with either stimulus. Stretch-dependent IL-3 release was confirmed with ELISA and blocked by P2X7R antagonists A438079 and Brilliant Blue G (BBG), implicating autostimulation of the P2X7R in stretch-dependent IL-3 release. Neuronal IL-3 release triggered by BzATP required extracellular calcium. The IL-3Rα receptor was expressed on retinal ganglion cells but not astrocytes, and both IL-3Rα and IL-3 itself were predominantly expressed in the retinal ganglion cell layer of adult retinal sections, implying autostimulation of receptors by released IL-3. While the number of surviving ganglion cells decreased with time in culture, addition of IL-3 protected against this loss of neurons. Expression of mRNA for IL-3 and IL-3Rα increased in rat retinas stretched with moderate intraocular pressure (IOP) elevation; BBG blocked the rise in IL-3, implicating a role for the P2X7R in transcriptional regulation in vivo. In summary, mechanical stretch triggers release of cytokines from neurons that can convey neuroprotection. Enhancement of these signals in vivo implicates P2X7R-mediated IL-3 signaling as an endogenous pathway that could minimize damage following neuronal exposure to chronic mechanical strain.